Engineering a more sustainable world through catalysis and green chemistry - Sheldon, Roger A. (J R Soc Interface, 2016)
The grand challenge facing the chemical and allied industries in the twenty-first century is the transition to greener, more sustainable manufacturing processes that efficiently use raw materials, eliminate waste and avoid the use of toxic and hazardous materials. It requires a paradigm shift from traditional concepts of process efficiency, focusing on chemical yield, to one that assigns economic value to replacing fossil resources with renewable raw materials, eliminating waste and avoiding the use of toxic and/or hazardous substances. The need for a greening of chemicals manufacture is readily apparent from a consideration of the amounts of waste generated per kilogram of product (the E factors) in various segments of the chemical industry. A primary source of this waste is the use of antiquated ‘stoichiometric’ technologies and a major challenge is to develop green, catalytic alternatives. Another grand challenge for the twenty-first century, driven by the pressing need for climate change mitigation, is the transition from an unsustainable economy based on fossil resources—oil, coal and natural gas—to a sustainable one based on renewable biomass. In this context, the valorization of waste biomass, which is currently incinerated or goes to landfill, is particularly attractive. The bio-based economy involves cross-disciplinary research at the interface of biotechnology and chemical engineering, focusing on the development of green, chemo- and biocatalytic technologies for waste biomass conversion to biofuels, chemicals and bio-based materials. Biocatalysis has many benefits to offer in this respect. The catalyst is derived from renewable biomass and is biodegradable. Processes are performed under mild conditions and generally produce less waste and are more energy efficient than conventional ones. Thanks to modern advances in biotechnology ‘tailor-made’ enzymes can be economically produced on a large scale. However, for economic viability it is generally necessary to recover and re-use the enzyme and this can be achieved by immobilization, e.g. as solid cross-linked enzyme aggregates (CLEAs), enabling separation by filtration or centrifugation. A recent advance is the use of ‘smart’, magnetic CLEAs, which can be separated magnetically from reaction mixtures containing suspensions of solids; truly an example of cross-disciplinary research at the interface of physical and life sciences, which is particularly relevant to biomass conversion processes.